A Signaling-Regulated, Short-Chain Dehydrogenase of Stagonospora nodorum Regulates Asexual Development - Tan, K.; Heazlewood, J.; Millar, A.; Thomson, G.; Oliver, Richard; Solomon, P. (American Society for Microbiology, 2008)
The fungus Stagonospora nodorum is a causal agent of leaf and glume blotch disease of wheat. It has been previously shown that inactivation of heterotrimeric G protein signaling in Stagonospora nodorum caused development defects and reduced pathogenicity [P. S. Solomon et al., Mol. Plant-Microbe Interact. 17: 456-466, 2004]. In this study, we sought to identify targets of the signaling pathway that may have contributed to phenotypic defects of the signaling mutants. A comparative analysis of Stagonospora nodorum wild-type and G alpha-defective mutant (gna1) intracellular proteomes was performed via two-dimensional polyacrylamide gel electrophoresis. Several proteins showed significantly altered abundances when comparing the two strains. One such protein, the short-chain dehydrogenase Sch1, was 18-fold less abundant in the gna1 strain, implying that it is positively regulated by G alpha signaling. Gene expression and transcriptional enhanced green fluorescent protein fusion analyses of Sch1 indicates strong expression during asexual development. Mutant strains of Stagonospora nodorum lacking Sch1 demonstrated poor growth on minimal media and exhibited a significant reduction in asexual sporulation on all growth media examined. Detailed histological experiments on sch1 pycnidia revealed that the gene is required for the differentiation of the subparietal layers of asexual pycnidia resulting in a significant reduction in both pycnidiospore size and numbers.